Characteristics of cruise ship fire propagation and emergency evacuation of personnel under different location conditions of ignition sources - Tianqi Liu (Case Studies in Thermal Engineering)
Cruise ships are densely populated places, once a fire occurs, it is difficult for people to escape and can easily cause casualties. In this paper, the changes in smoke, temperature, CO concentration, and visibility in cruise ship under different fire conditions are studied. The results show that when fires occur in different locations, the highest temperature on the burning deck exceeds 60 °C, the highest concentration of CO gas exceeds 0.040 %, and the lowest visibility value is less than 5 m. The area of high temperature and high CO concentration zones where the front of the cruise ship caught fire exceeded that of the rear and middle of the cruise ship. The diffusion speed of fire smoke far exceeds the speed of high temperature propagation, and the visibility of the burning deck first decreases to the dangerous range, followed by the ambient temperature and CO concentration. The death toll of the rear, middle, and front parts of the cruise ship caught fire are 8, 18, and 22 respectively, and the locations of personnel deaths are all within the burning deck corridors. Low visibility and high fire temperatures cause people to stay in high-temperature environments for too long, which is the main cause of death. The study provides reference for the setting of cruise ship fire-fighting facilities and the optimization of personnel evacuation routes.